Pelayanan Kebidanan Komprehensif Dengan Kehamilan Normal Di Puskesmas Caile Kecamatan Ujungbulu - Nurfadiji, Nurfadiji; Marwidah, Marwidah; Sari, Iramaya; Nurlaily, Andi; Amin, Mitra Asriani (Universitas Sumatera Barat, 2023)
Pregnancy, childbirth, the postpartum and newborn period are normal processes, but these conditions can become abnormal if monitoring is not carried out. Complications that can occur include irregular ANC visits, birth assistance by non-health workers, non-essential BBL services, non-continuous postpartum services and unscheduled use of contraceptives. Therefore, comprehensive midwifery care is needed, where this care is expected to be able to reduce complications that can occur during pregnancy and the use of contraceptives, and it is hoped that the mother can undergo all the processes normally. The aim is to provide comprehensive services to 35 year old Mrs “M” starting from pregnancy, postpartum, postpartum, newborn and contraceptive services. used in carrying out comprehensive midwifery care is a qualitative method with a case study approach (case study) Varney method with data collection techniques including observation, interviews, physical examination and documentation studies. The results of comprehensive midwifery care for Mrs